Intellectual property perspectives on the regulation of new technologies - Pistorius, Tana (ATRIP intellectual property, 2018)
Intellectual Property Perspectives on the Regulation of New Technologies explores the challenges that emerging technologies and technology-driven practices pose for traditional notions of intellectual property (IP) law and policy. This book exposes the intimate relationship between IP and technology and demonstrates how most substantial revisions to IP law have been driven by technological innovations. Authors offer perspectives from across the intellectual property law spectrum and address questions such as: is the law evolving in the right direction?; and is the regulation of emerging technologies supported by sound policy objectives? The resulting discussion exposes the disparate manner in which IP law has responded to challenges posed by innovation and new technologies. In Part I authors explore whether the regulation of new technologies has fundamentally altered the object and purpose of IP law, including the balance of interests. Part II focuses on the impact of digital technologies, specifically on copyright law and policy. Covering a diverse range of topics, this book will be of interest to scholars who are researching the relationship between technological development and IP law and practice. It will also be a useful resource for those who have an interest in the evolving nature of IP law.